Higher education in Libya: A study in spatial distribution patterns.: Higher education in Libya: A study in spatial distribution patterns. (jornal of the libyan geographical society, 2009)
Many researchers and specialists agree on the important and vital role of higher education in the development of individuals and societies, and on its importance in providing society with a highly efficient and skilled workforce. It also plays a fundamental role in any effective development, whether social, economic, or cultural (Al-Sunni, 2006). Over the past few decades, higher education has witnessed  Globally, it is growing rapidly, as a result of economic growth, the development of transportation and communication, and the increasing social demand for its services in both developed and developing countries.According to UNESCO estimates, the number of students enrolled in higher education institutions worldwide has increased from about half a million students, representing 1% of the total population of higher education age (18-24 years) in 1900, to about 100 million students, representing 20% ​​of the total population of higher education age.(2000-2004, UNESCO). Higher education institutions currently represent the largest service sector in many countries worldwide, employing large numbers of people with diverse specializations and qualifications. As a result of social changes  With the rapid economic growth the world is currently experiencing, higher education has become an important service industry that attracts large numbers of students and drives increased diversity in educational and training programs.
Keywords: Higher education; development; Working hands; Efficient; skill; Economic growth; Developed countries; Developing countries